Finding, freezing and attaching assets a multi-jurisdictional handbook - Jørgensen, Jacob C. (Kluwer Law International, 2016)
Finding, freezing and attaching assets: A multi-jurisdictional handbook' is about how to find out whether a defendant has any assets before initiating costly litigation, arbitration, or insolvency proceedings, and how to freeze such assets with the aim of eventually enforcing a judgment or award. The globalization in trade relations has resulted in a steady increase in cross-border disputes and, due to the ease with which assets can be moved around the world with the help of online banking and fiduciary service providers, parties are increasingly finding themselves suing or being sued outside their home jurisdictions. As a result, there is increased interest among clients with regard to the finding and freezing of assets as the parties involved in commercial disputes these days are doing their best to expatriate assets as well as undermine enforcement. The purpose of this book is to provide the reader with as much information as possible on asset identification on a jurisdiction-by-jurisdiction basis and also on the client?s decision of whether or not to freeze assets once the assets have been identified.